Characteristics of full compensation and its association with total astigmatism: A cross-sectional study - Wu, Ziyun; Hu, Yuanyuan; Xu, Zihang; Sun, Wei; Wang, Yirong; Shao, Zhen; Liu, Yi; Yu, Mingkun; Si, Peiran; Huo, HuanHuan; Wang, Xingrong; Bi, Hongsheng (Frontiers in Public Health, 2023)
Objective To evaluate the characteristics of full compensation and its association with the prevalence of total astigmatism (TA), and to analyze the effects of TA on uncorrected distance visual acuity (UDVA). Methods With random cluster sampling based on a school-based cross-sectional design, children aged 4 to 18 years were recruited in September 2020, Shandong Province, China. TA, anterior corneal astigmatism (ACA), and ocular residual astigmatism (ORA) were converted to vectorial components (J0, J45), followed by an assessment of the compensatory effect of ACA by ORA. Astigmatism was defined as a cylinder that was better than or equal to 0.75 diopters (D). Logistic regression analysis was used to assess the related factors for children with full compensation, and the generalized linear model was used to assess the influence of TA on UDVA. Results Out of 4,494 eligible children, data of 4,145 children (92.3%, 9.23 ± 3.15 years, 50.4% boys) were included in the statistical analysis. The prevalence of TA (27.9%) increased significantly with age (Ptrend < 0.001). The distribution of full compensation in J0 and J45 components were similar (22.1% and 25.6%, respectively), which decreased with age (Ptrend < 0.001). The closer the refractive status was to emmetropization, the higher the proportion of full compensation and the lower the prevalence of TA were. Shorter axial length (J0: Odds Ratio (OR) = 0.76, 95% confidence interval (CI): 0.61 to 0.94, P = 0.010), better UDVA (J0: OR = 0.37, 95% CI: 0.21 to 0.65, P < 0.001; J45: OR = 0.34, 95% CI: 0.20 to 0.59, P < 0.001), and longer average corneal curvature radius (J0: OR = 3.72, 95% CI: 2.18 to 6.34, P < 0.001; J45: OR = 2.82, 95% CI: 1.67 to 4.76, P < 0.001) were associated with full compensation. Higher TA was associated with a worse UDVA (β = 0.03, 95% CI: 0.02 to 0.04, P < 0.001). Conclusions The prevalence of TA gradually increased with age, and showed a U-shaped distribution with increased refraction. Full compensation was associated with smaller TA and better UDVA. This indicated that considering the compensatory effect of ORA is vital for astigmatism correction in clinical work, which may improve the visual quality.